STORYTELLING IN JOURNALISM AS THE NEW GENRE PROCEDURE - Mirkov, Lidija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
In this paper, the definitions of storytelling and journalistic storytelling are given in the scientific context, together with the distinction between these concepts in relation to the media. In order to determine the narration in the media, it is necessary to explain what narration means in other fields of research. The most common use of these terms is in literary and linguistic studies, but even some authors in these fields believe it is quite possible that their fields have set up a monopoly on the notion of narration, and that research can be extended to all genres of reality in which it occurs. In the mid-nineties of the 20th century and in the past decade, a new phenomenon in the presentation of media content has emerged in the professional and academic circles around the world: journalistic storytelling. The common definition of similar terms might be the narrative discourse. Under this term, we mean a romanticized, soft image of important events that the media are reporting about. In this paper, journalistic storytelling is defined for the first time as a non-fictitious romanticized journalistic discourse. It is non-fictitious because it communicates information about the real world, without pretending to present one of them as imaginary or created or subjective - on the contrary, it is claimed that what is told is the reality. The genre changes in journalism, from the narration of short stories to factography, and from factography to narrative news, show that journalism is a creative profession in the discursive recording of history.